Perang-perang atas Laut, Menghitung Tantangan pada Manajemen Sumberdaya Laut di Era Otonomi: Pelajaran dari Kepulauan Kei, Maluku Tenggara - Dedi Adhuri (Antropologi Indonesia, 2005)
Natural resource management discourse and practice, as in politics but in different level, are shifting from centralized to local autonomy. Consequently, local government has to undertake many tasks. One important task is to formulate natural resource management policy that can contribute to enhance social welfare without disturbing natural resource sustainability. Hence, it is useful to evaluate existing management practices to learn its weaknesses and strengths as the basis in formulating new management policy. This article discussed conflict potential among stakeholders in the exploitation of sea natural resources in Kei islands, Southeast Mollucan. By analyzing the conflict, the discussion will identify stakeholders and power relations among them (interests, strategies and resource controls) to reveal challenges in natural resource management practices in the local autonomy era. Key words: conflict; natural resources management; regional autonomy; agency.